The impact of robots in Latin America: Evidence from local labor markets - Irene Brambilla; Andrés César; Guillermo Falcone; Leonardo Gasparini (Universidad Nacional de La Plata, Centro de Estudios Distributivos, Laborales y Sociales (CEDLAS), 2023)
We study the effect of robots on labor markets in Argentina, Brazil, and Mexico, the major robot users in Latin America, during the period 20042016. We exploit spatial and time variations in exposure to robots arising from initial differences in industry specialization across geographic locations and the evolution of robot adoption across industries, to estimate a causal effect of robots on local labor market outcomes. We find that district's exposure to robots causes a relative deterioration in labor market indicators such us unemployment and labor informality. We document that robots mainly replace formal salaried jobs, affecting young and semi-skilled workers to a greater extent, and that informal employment acts as a buffer that prevents a larger increase in unemployment.
Keywords: J23; J24; J31; J46; O14; O17; R10; 330; Robot Adoption; Local Labor Markets; Latin America; Unemployment; Informality